Assessment of the contextual effects on the prevalence of periodontitis: a systematic review - Leonardo Vilar FILGUEIRAS; Willian KONFLANZ; Alex Nogueira HAAS; Roger Keller CELESTE (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study reviews the influence of contextual factors on periodontitis based on a systematic search of studies recorded in the PubMed, Scopus, Web of Science, and EMBASE databases. Periodontitis was assessed by clinical attachment loss and probing depth for studies with data on the socioeconomic status (SES) of a specific area (area-level SES) or dental care service (service-level) in a catchment area among individuals aged 18 and over. Two independent reviewers performed study selection, data extraction, and assessment of methodological quality. Of the 646 articles identified, 13 were included in the systematic review, representing 101,362 individuals from five countries (USA, UK, Brazil, China, and Uruguay). A higher prevalence of periodontitis was described in lower SES neighborhoods, more deprived postcodes, and poorer provinces. Gini Index results were mixed and inconclusive. Three studies showed that higher coverage of primary dental care at the municipal level was associated with a lower prevalence of periodontitis. Contextual factors at the area-level SES and dental care service might influence periodontitis, but the existing evidence is unclear. The contextual effect is important for periodontal health and may contribute to the prevalence of periodontitis, independent of well-known risk factors and individual levels.